Globalization Democracy and the Arab Spring in Libya - Ayanda, Abraham B. (Journal of Contemporary International Relations and Diplomacy, 2025)
This study explores the impact of globalization on democracy and democratization in post-Arab Spring Libya. While the 2011 uprising was fueled by aspirations for political freedom, justice, and inclusive governance, it ultimately resulted in state collapse, militia dominance, and prolonged instability. Using qualitative content analysis based on secondary data—including academic literature, policy documents, and media reports—the study critically investigates how global forces shaped both the revolutionary moment and the trajectory of Libya’s failed democratic transition. Anchored in Structural Realism and Democratic Transition Theory, the paper argues that Libya’s democratization crisis reflects both internal institutional fragility and external geopolitical contradictions. Specifically, it demonstrates how international interventions promoted regime change without ensuring the foundational support necessary for democratic consolidation. The findings reveal that fragmented political authority, weak institutions, and the strategic interests of global and regional actors obstructed the development of an inclusive political order. The study contributes to the scholarship on post-conflict democratization by emphasizing the limits of externally driven transitions in fragile states. It recommends an institutionally grounded, context-sensitive approach to democratization that prioritizes local ownership and long-term governance development. Libya’s experience offers a critical case for understanding the paradoxes of globalization and the contested outcomes of democracy promotion in the Global South.